The factors determining the effectiveness of teaching, German as the foreign language in primary school education - Dombosi, Kornélia; Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2014)
The factors determining the effectiveness of teaching, German as the foreign language in primary school education motivating teaching, dramatization, children acting, dance, DIY and encampment abroad. The method of the foreign language teaching has changed during the last 30 years. The question of the foreign language teaching has not lost actuality, as we can experience that some of the students learn 9-10 years to reach the intermediate level in a language. The long-term motivations of the students are difficult to maintain, that is why my purpose was to find platforms and methods, which help to move forward the successful language teaching. I have put my research on the basis of observation. Most of my ideas were tested, and I used in my exercises.
Keywords: German as a foreign language; language teaching; primary school education